Performance evaluation of marigold pre-breeding lines for total carotenoids content, flower yield and associated traits - DEDHIA, LABDHI; ARIVALAGAN M.; TEJASWINI P. (Journal of Ornamental Horticulture, 2024)
Marigold with orange-coloured petals are gaining momentum among the growers and industries due to the presence of high amount of total carotenoids. Study was carried out to find the variability for carotenoid content and associated characters in marigold pre-breeding lines and their heritability for effective utilization in future breeding programme. Wide variability was observed for flower yield and associated traits. High genotypic and phenotypic coefficient of variations, heritability and genetic advance over mean were recorded for plant height, total No. of flowers, flower yield per plant and No. of seeds per capitulum indicating presence of higher genetic variability and these traits can be further improved through selection. Moderate heritability was recorded for traits like plant spread, No. of branches and flower diameter, suggesting their improvement through further hybridization and selection. Total carotenoid content among the pre-breeding lines ranged between 1.35 -2.49 g/100g DW and was found to be positive significant correlated with No. of secondary branches, flower diameter and flower yield per plant governed with moderate to low heritability. Based on the mean performance of the traits, six pre-breeding lines IIHRM0 2335 (2.28 g/100g DW), IIHRM 2-3S (2.49 g/100g DW), IIHRM 2-3F (2.06 g/100g DW), IIHRMO 2340 (2.07 g/100g DW), IIHRMO 2336 (2.03 g/100g DW) and IIHRMO 232 (2.02 g/100g DW) were identified that were rich in total carotenoid content along with the associated traits, which can be utilized as seed and/or pollen parent for development of carotenoid-rich marigold hybrids.